The Relationship between Knowledge, Low-Salt Dietary Behavior and Hypertension in Teluknaga Public Health Center - Siti Aulia Intan Nabilla; Popy Irawati (Universitas Muhammadiyah Tangerang, 2020)
Hypertension is a condition where a person's blood pressure is above the normal or optimal limit of 120 mmHg for systolic and 80 mmHg for diastolic. This study aims to determine the relationship of knowledge and consumption behavior of a low-salt diet to the incidence of hypertension in the area of Puskesmas Teluknaga. This research is a kind of quantitative research with a cross-sectional study design. The sampling technique using the number of samples that meet the criteria of inclusion and exclusion. The samples of this study amounted to 41 respondents from the average number of populations of 45 respondents. Instruments in this study using questionnaires. The results of this study indicate that respondents who have poor knowledge with negative behavior of 11 respondents (68.8%), knowledge of less good with positive behavior as much as 5 respondents (31.3%), good knowledge with negative behavior of 7 respondents (28.0%) and good knowledge with negative behavior as much as 18 respondents ( 72.0%) negative behavior does not of knowledge of respondents who have a basic level of education, but the behavior of negative respondents can be judged from the level of self-awareness. The result of the Chi-Square statistic test shows that there is a correlation between knowledge and consumption behavior of low salt diet to hypertension event in the area of Puskesmas Teluknaga with p-value= 0,033 (P-Value <α 0,05).Keywords: Hypertension, Knowledge, Behavior